STYLISTIC ANALYSIS OF POEMS - Turgunaliyeva Kristina Ma’rufjonovna (Galaxy International Interdisciplinary Research Journal, 2023)
There are different branches of linguistics. Among them, stylistics is distinguished by color. Stylistics (Greek: stylos - writing, writing stick), stylistics, methodology - researches the language styles of linguistics, studies the essential features of the functional layering of the language on the lexical-phraseological, phonetic, morphological, word-formation and syntactic levels from the synchronic and diachronic points, the development of the methods of social life in various literary situations, in various genres of written literature.